Empowering roots—Some current aspects of root bioenergetics - Wegner, Lars H. (Frontiers in Plant Science, 2022)
Roots of higher plants provide the shoot with nutrients and water. In exchange, they receive photosynthates, which serve both as energy source and building blocks for maintenance and growth. While studies in plant bioenergetics used to focus on photosynthesis, several more recent findings also aroused or renewed interest in energy conversion and allocation in roots. Root building costs were identified as a long-undervalued trait which turned out to be highly relevant for stress tolerance and nutrient use efficiency. Reduced building costs per root length (e.g. by aerenchyma formation or by increasing the cell size) are beneficial for exploring the soil for nutrient-rich patches, especially in low-input agrosystems. Also, an apparent mismatch was frequently found between the root energy budget in the form of the ATP pool on the one side and the apparent costs on the other side, particularly the costs of membrane transport under stress conditions, e.g. the Na+ detoxification costs resulting from Na+ sequestration at the plasma membrane. Ion transport across the plasma membrane (and also endomembranes) is coupled to the proton motive force usually believed to be exclusively generated by H+ ATPases. Recently, an alternative mechanism, the biochemical pH clamp, was identified which relies on H+ formation and binding in the apoplast and the cytosol, respectively, driven by metabolism (so-called active buffering). On this background, several aspects of root bioenergetics are discussed. These are (1) root respiration in soil, with a critical view on calorimetric versus gas exchange measurements; (2) processes of energy conversion in mitochondria with a special focus on the role of the alternative oxidases which allow adjusting carbon flow through metabolic pathways to membrane transport processes and (3) energy allocation, in particular to transport across the plasma membrane forming the interface to soil solution. A concluding remark is dedicated to modelling root bioenergetics for optimizing further breeding strategies. Apparent ‘energy spoilers’ may bestow the plant with an yet unidentified advantage only unfolding their beneficial effect under certain environmental conditions.